If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -6x = 25 Combine like terms: x + -6x = -5x -5x = 25 Solving -5x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-5'. x = -5 Simplifying x = -5
| 9/14cos | | .9x-.9(5-x)=3.6 | | 8/2x=0 | | 5x(x-5)-11(x-5)= | | x*x=2*x | | 2v+42=-3(v-9) | | 3/10m-2/5=1/10. | | 4.5x^3+2.2x=3454 | | ((12(b^5)y)/(y^3))/(4b^4/3y) | | 7x-4=14-2x | | m+x=mx | | 3x+(x-1)=4(x-1) | | 4x^2=32y | | 45k+27=18k^2 | | 5x-3-2x)/7=24 | | 1/3(6x-15)=1/2(1ox=4) | | R^2-3r-15=0 | | 2x-4y=-76 | | x+6=5(y-6) | | 7(3x+21)+6(x+53)=546 | | 220/10 | | 2(4z-6)=170-46 | | Y=2x-5x | | m^3=64m | | 8(5k-5)=-40-7k | | 8=9u-u | | 5+3x=4x-7 | | cos29=17.3/x | | 45=x+(x-2)+(x-4) | | -14-(-20)=x/4 | | 237760+26x=3000000 | | C=(2a-3b)/2 |